Effect of Electronic Acceptor Segments on Photophysical Properties of Low-Band-Gap Ambipolar Polymers - Yuanzuo Li; Jingang Cui; Jianing Zhao; Jinglin Liu; Peng Song; Fengcai Ma (The Scientific World Journal)
Stimulated by a recent experimental report, charge transfer and photophysical properties of donor-acceptor ambipolar polymer were studied with the quantum chemistry calculation and the developed 3D charge difference density method. The effects of electronic acceptor strength on the structure, energy levels, electron density distribution, ionization potentials, and electron affinities were also obtained to estimate the transporting ability of hole and electron. With the developed 3D charge difference density, one visualizes the charge transfer process, distinguishes the role of molecular units, and finds the relationship between the role of DPP and excitation energy for the three polymers during photo-excitation.